2019
DOI: 10.1371/journal.pone.0225120
|View full text |Cite
|
Sign up to set email alerts
|

Study on characteristics of fire plume in building facade window under lateral blow

Abstract: The overflow of the flame plume from the window is the main cause of the vertical spread of the fire on the facade of the building. This paper considers the geometry of the window by taking measures to prevent the flame from propagating along the vertical wall. In this paper, a residential building is taken as an example to evaluate the flame plume characteristics through experimental tests and numerical simulations. The objective of the present study is to study the flame plume characteristics under the air b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 22 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Both experimental and simulation results showed that for a given cavity width, heat release rate and geometry of the window opening were the two key factors in determining the plume trajectory. Li and Bai [23,24] studied the characteristics of window plumes based on the under-ventilated compartment fires. But, their research focused on the side wind effect on the flow behavior of the window plume under free working conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Both experimental and simulation results showed that for a given cavity width, heat release rate and geometry of the window opening were the two key factors in determining the plume trajectory. Li and Bai [23,24] studied the characteristics of window plumes based on the under-ventilated compartment fires. But, their research focused on the side wind effect on the flow behavior of the window plume under free working conditions.…”
Section: Introductionmentioning
confidence: 99%